Prefrontal corticotropin‐releasing factor neurons impair sustained attention via distal transmitter release. (1st June 2021) - Hupalo, Sofiya; Spencer, Robert C.; Berridge, Craig W.
Abstract: The prefrontal cortex (PFC) supports cognitive processes critical for goal‐directed behavior. Although the PFC contains a high density of corticotropin‐releasing factor (CRF) neurons, their role in cognition has been largely unexplored. We recently demonstrated that CRF neurons in the caudal dorsomedial PFC (dmPFC) of rats act to impair working memory via activation of local CRF receptors. However, there is heterogeneity in the neural mechanisms that support the diversity of PFC‐dependent cognitive processes. Currently, the degree to which PFC CRF neurons impact other forms of PFC‐dependent cognition is unknown. To address this issue, the current studies examined the effects of chemogenetic manipulations of PFC CRF neurons on sustained attention in male rats. Similar to working memory, activation of caudal dmPFC CRF neurons impaired, while inhibition of these neurons or global CRF receptor antagonism improved, sustained attention. However, unlike working memory, the sustained attention‐impairing effect of PFC CRF neurons was not dependent on local CRF receptors. Moreover, CRF infusion into the caudal dmPFC or other medial PFC subregions had no effect on task performance. Together, these observations demonstrate that while caudal dmPFC CRF neurons impair both working memory and sustained attention, these actions involve distinct neural circuits (local CRF release for working memory and extra‐PFC release for sustained attention). Nonetheless, the procognitive actions of systemically administered CRF antagonists across both tasks are similar to those seen with attention deficit hyperactivity disorder‐related treatments. Thus, CRF antagonists may have potential for use in the treatment of PFC cognitive dysfunction. Abstract : Chemogenetic activation of caudal dmPFC CRF neurons impairs both sustained attention and working memory. Conversely, chemogenetic inhibition of these neurons or global administration of CRF antagonists improves these cognitive processes. However, the projection pathways involved in these actions are highly distinct, involving local CRF neurotransmission in the case of working memory and CRF release outside the PFC in the case of sustained attention.